PENGARUH INCOME SMOOTHING, KEBIJAKAN DEVIDEN, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP EARNINGS RESPONSE COEFFICIENT DAN FUTURE EARNINGS RESPONSE COEFFICIENT - Amrie Firmansyah; Vinola Herawaty (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2016)
This study is aimed to examine the effect of income smoothing, dividend policy, leverage and firm size on earnings response coefficient and future earnings response coefficient. The population used in this study are all non:financial companies listed in Indonesia Stock Exchange.from 2007 until 2013. The main data used in this research is the data in 2011 and 2012. This research uses financial data from 2007 because the data required in the calculation of income smoothing over the last 5 years for income smoothing in 2011, while stock returns data in 2013 reflects the future returns for 2012. Completed and selected financial data this research are 103 companies, so that the samples in this research using 2-year period are 206. For examining data, this research uses panel data regression model. After running chow test and hausman test, the most suitable method for the regression is fixed effects method. This research shows that income smoothing has positive influence significantly on ERC, but has negative influence significantly on FERC. While, leverage has no influence significantly on ERC, but has negative influence significantly on FERC. Furthermore both dividends andfirm size have no influence on ERC and FERC.